Computer produced choropleth maps with overlays: An aid in urban and regional analysis - Lovingood, Paul E. (The Greek Review of Social Research, 1975)
Modern urban and regional analysis demands a rapid and accurate system of mapping a wide range of societal information. Conventional cartography cannot satisfy this demand and the planner and researcher have turned to the computer. CMAP is only one of many systems of computer mapping but it is easily adapted for use with overlays. The advantage of this system is that once the computer base map is operational only the overlays need to be changed to vary the maps. All of the South Carolina maps presented in this paper were produced on the same computer base map.